The potential for energy savings in U.S. houses by using isothermal dehumidification. (3rd July 2021) - Thiel, Gregory P.; Atkinson, Christopher
Abstract : Potential energy savings achievable by using isothermal dehumidification instead of conventional air conditioning systems are modeled on a technology-agnostic basis. First, we use simple thermodynamics to model potential device-level energy savings by dehumidifying isothermally instead of by sub-dew-point cooling. A model for dehumidification demand in a prototypical house is then developed, and the device-level model is applied to the house under relevant climactic norms and weather extremes. Finally, we model all U.S. houses by coupling the household model with a statistical model for air infiltration representing all single-family, detached homes in the United States. The results show potential nationwide electricity savings of 8–25 TWh e / y, or 5–14% of electricity usage for space cooling in U.S. single-family homes, depending on weather. The results also display large regional differences, with moist hot climates having the greatest potential absolute energy savings, but moist temperate climates having the greatest potential relative energy savings. Individual houses with high balance-point temperatures in moist climate zones are likely to derive the greatest benefit by using isothermal dehumidification over conventional systems. Ultimately, this technology-agnostic analysis provides fundamental, thermodynamics-based insight into where, when, and how isothermal dehumidification devices can reduce the energy and greenhouse gas footprints of space cooling.